Reconstruction of the High-Osmolarity Glycerol (HOG) Signaling Pathway from the Halophilic Fungus Wallemia ichthyophaga in Saccharomyces cerevisiae - Konte, Tilen; Terpitz, Ulrich; Plemenitaš, Ana (Frontiers in Microbiology, 2016)
The basidiomycetous fungus Wallemia ichthyophaga grows between 1.7 M and 5.1 M NaCl and is the most halophilic eukaryote described to date. Like in other fungi, in W. ichthyophaga, changes in environmental salinity are detected mainly by the evolutionarily conserved high-osmolarity glycerol (HOG) signaling pathway. In Saccharomyces cerevisiae, the HOG pathway has been extensively studied in connection to osmotic regulation, with a valuable knock-out strain collection established. In the present study, we reconstructed the architecture of the HOG pathway of W. ichthyophaga in suitable S. cerevisiae knock-out strains, through heterologous expression of the W. ichthyophaga HOG pathway proteins. Compared to S. cerevisiae, where the Pbs2 (ScPbs2) kinase of the HOG pathway is activated via the SHO1 and SLN1 branches, the interactions between the W. ichthyophaga Pbs2 (WiPbs2) kinase and the W. ichthyophaga SHO1 branch orthologs are not conserved: as well as evidence of poor interactions between the WiSho1 Src-homology 3 (SH3) domain and the WiPbs2 proline-rich motif, the absence of a considerable part of the osmosensing apparatus in the genome of W. ichthyophaga suggests that the SHO1 branch components are not involved in HOG signaling in this halophilic fungus. In contrast, the conserved activation of WiPbs2 by the S. cerevisiae ScSsk2/ScSsk22 kinase and the sensitivity of W. ichthyophaga cells to fludioxonil, emphasize the significance of two-component (SLN1-like) signaling via Group III histidine kinase. Combined with the protein modeling data, our study reveals conserved and nonconserved protein interactions in the HOG signaling pathway of W. ichthyophaga and therefore significantly improves the knowledge of hyperosmotic signal processing in this halophilic fungus.